(untitled) (Neo Scientific Peer Reviewed Journal, 2024)
One of the most enduring characteristics of O. Henry’s short stories is their unexpected resolutions. They frequently have unexpected endings and have unique narratives. O. Henry gained recognition for his use of humor, his ability to tell stories in a distinctive way, and his unexpected yet logical conclusion. Because of reality’s irony and the resurgence of human nature, his superb writing technique is more evident. Later realistic fiction developed in a pluralistic manner, facilitated by the O. Henry-esque finale. This pivotal point’s extremely crucial ending further emphasizes the usefulness of world literature’s response to society. This article examines the influence of O. Henry’s writing on later generations of writers and the American national mentality of the late 19th and early 20th centuries. O. Henry’s literary works, known for their wit, irony and careful observation of human nature, continue to captivate readers around the world. Through an analysis of O. Henry’s thematic concerns, narrative techniques, and portrayal of characters, we will illuminate his enduring literary legacy and his significance within the broader context of American literature.